PENGARUH KEPERCAYAAN MEREK, PERIKLANAN, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK MINUMAN ISOTONIK MIZONE DI KOTA PALU - FAUZAN, Muhammad RIZKY (Fakultas Ekonomi Universitas Tadulako, 2015)
The aim of the research is to analyze the influence of brand trust (X1), advertising (X2), and product quality (X3) on purchase decision (Y) both simultaneously and partially. Research method is descriptive causal with a sample size of 115 respondents who are selected using purposive sampling technique. The results of the study show that: 1) brand trust, advertising, and product quality simultaneously have positive and significant influence on purchase decision of customer of Mizone isotonic drink in Palu; 2) brand trust has positive and significant influence on purchase decision of customer of Mizone isotonic drink in Palu; 3) advertising has positive and significant influence on purchase decision of customer of Mizone isotonic drink in Palu; 4) product quality has positive and significant influence on purchase decision of customer of Mizone isotonic drink in Palu.